Fieldwork experiences researching cybercriminals - Moneva, Asier (Fieldwork experiences in criminology and security studies, 2023)
Cybercriminals are an elusive population to study. This makes social research with cybercriminals as valuable as it is scarce. To stimulate research on cybercriminals, it is important that researchers share their insights on successful and unsuccessful approaches, strategies, and techniques. This chapter collects our fieldwork experiences researching cybercriminals, potential cybercriminals, hackers, and hacktivists. After presenting the phases of our fieldwork, we outline six research techniques we have applied and discuss the ethical issues involved. We conclude with some lessons learned and methodological perspectives to guide future research.